Training and recreation infrastructure for the First Mounted Squad of the National Police of Peru, in search of quality training and service, in the city of Tacna - Salinas Maldonado, Yomara Ursula (2014)
Objective: The objective was to propose and develop the project arquitectonic Infraestructure Comprehensive Instruction for the Mounted Police of Peru, with the aim of enabling the optimization of the levels of service quality educational institution for its members; likewise by this optimization improved quality of community service is channeled. Method: The methodology used in the research was, purposeful-descriptive-analytic by which the present situation of the Special Service Unit was identified as well as the landscape of social insecurity, a diagnosis that ultimately led to the approach of the architectural project was formulated . Result: The Peru throughout Latin America gets the 3rd place as the indicator of crime victimization, another important indicator is homicide, being Tacna city with the highest percentage of incidents recorded (35%). There is a need to strengthen the functionality of the police to ensure domestic order in the territory, for it is required of a police reform that allows the approach , formulation , implementation of plans, programs and projects as it is, allowing the effectiveness of the institution. Conclusion : We conclude with project development that meets the physical-spatial problem of the institution and facilitates the optimization of educational services and community.